Evaluating Effect of Social Support Programs Based on the Roy\'s Adaptation Model on Patients with Breast Cancer: A Systematic Review - Mohsen Adib-Hajbaghery; Fatemeh Maghsoud; Zahra Batooli (Golestan University of Medical Sciences, 2021)
Background: Many women become hopeless and are unable to adapt to disease after diagnosis of breast cancer. Social support plays a major role in adaption of patients to cancer. The present systematic review aimed to determine effects of social support programs based on the Roy's adaptation model on patients with breast cancer. Methods: In the present systematic review, articles published in English that have been indexed in PubMed, Scopus and Web of Science databases until the end of September 2019 were included. Searches were made using the following keywords: "Social Support", "Roy Model", "Breast Cancer" and their synonyms. The publications were selected through screening, selection, quality evaluation and data extraction. Interventional and qualitative studies were included in the study, which used the Roy's adaptation model for social support in women with breast cancer or used the model for evaluation the consequences of implementing support programs. Overall, 98 articles published were reviewed. After exclusion of unrelated articles, five articles were included in the analysis. Results: Of five high-quality articles, three were qualitative and two were interventional. The findings indicated that the implementation of support programs based on the Roy's adaptation model had beneficial effects on patients' adaptive responses, attitudes towards breast cancer, spiritual health, mood and loneliness. Conclusion: Implementing support programs can positively affect the adaptation of patients with breast cancer. Therefore, social support based on the Roy's adaptation model can be utilized as a non-invasive, non-pharmacological, cost-effective and comprehensive nursing intervention to provide support for patients with breast cancer.